The problem of the relationship of matter and consciousness From the point of modern information theory (Journal of Philosophy Culture and Political Science, 2024)
In the article, the authors propose to consider the problem of the relationship between matter and consciousness from a slightly different angle. Known. that the results obtained to date in the field of studying neural networks and artificial intelligence force us to largely reconsider the content of the concept of “consciousness”.The emergence of modern information processing systems, including the most highly developed ones, essentially represent certain fundamental properties inherent in matter as such. This conclusion is based on experimental data proving that a complex system of any nature becomes such provided that it is converted into a neural network or its analogue. In this context, “consciousness” corresponds to only one of the levels of the complex hierarchy of systems of perception and information processing that permeate the universe from the physical and chemical level to the level of the Universe.It has been suggested that, in accordance with existing well-known theories about the world spirit, it is permissible to interpret the so-called World Spirit (according to Hegel) by considering the Universe as a kind of neural network that forms a certain system of perception and processing of information.Key words: matter, consciousness, neural network, information theory, categorical apparatus, dialectics, undefined concepts.